2020
DOI: 10.1159/000511656
|View full text |Cite
|
Sign up to set email alerts
|

The Choice of Population and Outcomes in Neonatal Trials on Hyperbilirubinemia: Are They Relevant? An Analysis of Cochrane Neonatal Reviews

Abstract: <b><i>Background:</i></b> Neonates with jaundice are usually managed according to their serum bilirubin despite an unclear overall correlation between bilirubin levels and patient-important outcomes (PIOs) such as kernicterus spectrum disorder (KSD). <b><i>Objectives:</i></b> We examined data from Cochrane Neonatal reviews to assess whether conditions that constituted KSD were included as key outcomes and how commonly they occurred in the population studied. <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…The effect on the affected individual’s families is enormous, and the need for lifelong support continues after parents and close family members have passed on or left the close family circle. Contrary to Lai et al’s [3] contention that studies in low-risk populations are a waste of resources, and we are of the opinion that low-risk populations are the very population groups which should be targeted.…”
contrasting
confidence: 60%
See 1 more Smart Citation
“…The effect on the affected individual’s families is enormous, and the need for lifelong support continues after parents and close family members have passed on or left the close family circle. Contrary to Lai et al’s [3] contention that studies in low-risk populations are a waste of resources, and we are of the opinion that low-risk populations are the very population groups which should be targeted.…”
contrasting
confidence: 60%
“…In the current issue of Neonatology, Lai et al [3] examined data from published Cochrane Neonatal reviews that evaluated interventions for neonatal jaundice. Of 431 outcomes reported in 78 randomized controlled trials up to November 2017, Lai et al [3] found that only 40 (9.2%) had research objectives based on the dreaded patient-important outcome, KSD, while no infant actually developed KSD across all the studies. Furthermore, over half the trials were performed in populations with very low risk of KSD.…”
mentioning
confidence: 99%
“…While the trial data do not currently support widespread adoption of this technology, further research could determine whether this promising approach is feasible, acceptable, safe, and effective in remote and rural as well as urban settings with restricted resources for conventional phototherapy, particularly in sub-Saharan Africa and South Asia. Trials should be simple and pragmatic and aim to evaluate outcomes, including bilirubin encephalopathy and mortality, of most importance to infants, their families, and health services [15]. Related questions may include exploring whether there is a subgroup of low-risk infants with mild jaundice who can be safely treated at home with filtered sunlight phototherapy.…”
Section: Commentarymentioning
confidence: 99%
“…Some areas of neonatal research, however, assess “surrogate,” rather than infant- and family-important, outcomes more commonly. For example, trials of interventions to prevent bilirubin encephalopathy and kernicterus spectrum disorder have tended to report the effect on serum bilirubin levels rather than on adverse neurodevelopmental outcomes [30]. While this may be a pragmatic approach given the rarity of kernicterus spectrum disorder, particularly in countries with well-resourced perinatal health services, evidence exists that even very plausible surrogate outcomes such as hyperbilirubinaemia may not necessarily predict infant-important outcomes accurately [31, 32].…”
Section: Direct Relevance Of Evidence To the Target Populationmentioning
confidence: 99%